Kyoto2.org

Tricks and tips for everyone

Reviews

Is csc the opposite of sin?

Is csc the opposite of sin?

Cosecant is the reciprocal of sine. Its abbreviation is csc. To determine csc, just flip sin over. Secant is the reciprocal of cosine.

What is the ratio of cosecant of θ?

1sinθ
Allied to these are the three reciprocal ratios, cosecant, secant and cotangent: cosecθ=hypotenuseopposite,secθ=hypotenuseadjacent,cotθ=adjacentopposite. cosecθ=1sinθ,secθ=1cosθ,cotθ=1tanθ.

Is cosecant a cos or sin?

The functions are usually abbreviated: sine (sin), cosine (cos), tangent (tan) cosecant (csc), secant (sec), and cotangent (cot)….Math2.org Math Tables:

sine(q) = opp/hyp cosecant(q) = hyp/opp
cosine(q) = adj/hyp secant(q) = hyp/adj
tangent(q) = opp/adj cotangent(q) = adj/opp

What is cosec function?

The cosecant function is the reciprocal of the trigonometric function sine. Cosecant is one of the main six trigonometric functions and is abbreviated as csc x or cosec x, where x is the angle. In a right-angled triangle, cosecant is equal to the ratio of the hypotenuse and perpendicular.

What is secant and cosecant?

Cosecant is the reciprocal of sine. Secant is the reciprocal of cosine.

What is the reciprocal of csc?

The reciprocal identities are: csc(x) = 1/sin(x), sec(x) = 1/cos(x), and cot(x) = 1/tan(x).

What is csc theta?

Cosecant Function: csc(θ) = Hypotenuse / Opposite. Secant Function: sec(θ) = Hypotenuse / Adjacent.

What is a cosecant in math?

1 : a trigonometric function that for an acute angle is the ratio between the hypotenuse of a right triangle of which the angle is considered part and the leg opposite the angle.

What is cosecant and cotangent?

Cosecant is the reciprocal of sine. Secant is the reciprocal of cosine. Cotangent is the reciprocal of tangent. When solving right triangles the three main identities are traditionally used.

How do you solve csc?

Cosecant Formula Thus, the cosecant of angle α in a right triangle is equal to the length of the hypotenuse c divided by the opposite side a. To solve csc, simply enter the length of the hypotenuse and opposite side, then solve. This formula might look very similar to the formula to calculate sine.

Related Posts